(untitled) (Biological Sciences - PJSIR, 2009)
In the study of the extractive separation of Al(III) and Ni(II) by di-2-ethylhexyl phosphoric acid D2EHPA- kerosene from aqueous fluoride medium, about 94% Al(III) and 2% Ni(II) were extracted with 0.3 M D2EHPA (pH 2.1 and temperature 30±1 °C). Extraction of Ni(II) decreased with increasing extractant concentration. D2EHPA-kerosene- fluoride system showed better extraction of Al(III) with higher extractant concentration and aqueous pH and vice versa for the extraction of Ni(II). The maximum separation factor (b 1380) was obtained for Al(III) at 20 °C and decreased to (b 732) at 60 °C. The separation of Al(III) from Ni(II) was favoured at normal temperature. Extraction followed the order Al(III) >>>Ni(II). About 99% stripping of Al(III) was attained from the loaded 0.20 M D2EHPA. Much faster extraction of Al(III) compared to Ni(II) and preferential loading were shown by D2EHPA-kerosene in the presence of fluoride ion in the aqueous phase. Separation of Al(III) was the most outstanding from Ni-Al-F-complex solution.